Development and evaluation of PCR test for detection of Taylorella equigenitalis - Bleumink-Pluym, N M; Werdler, M E; Houwers, D J; Parlevliet, J M; Colenbrander, B; van der Zeijst, B A (Journal of clinical microbiology, 1994)
A PCR for the detection of Taylorella equigenitalis, the causative agent of contagious equine metritis, was developed and evaluated. A genus-specific primer-probe set was derived from the 16S ribosomal DNA sequences. The PCR was specific and amplified a 585-bp product from all 64 available T. equigenitalis isolates. This PCR product hybridized with a specific probe in a dot spot assay. A variety of microorganisms from the genital tracts of horses or with a close phylogenetic relationship to T. equigenitalis did not yield a visible PCR product and were all negative in the dot spot hybridization assay. The results of the PCR assay were compared with those of culture by using 191 genital swabs from horses of several breeds. We demonstrate that the sensitivity of the PCR assay is superior to that of culture. The assay is most sensitive when DNA from culture plates incubated for at least 2 days is used. Of the tested samples, 1.5% were positive in the culture assay, whereas 35% were positive in the culture PCR assay. PCR-positive samples were obtained from all breeds tested. This means that many T. equigenitalis-carrying horses go unidentified by the current culturing technique. This affects current views about the spread and control of T. equigenitalis.